Efforts to strengthen community and health worker participation in the SIAGA DBD application utilization - Lilik Zuhriyah; Alidha Nur Rakhmani; Agwin Fahmi Fahanani; Siti Azwa Zafira; Disa Yuni Shabrina Issaray (University of Merdeka Malang, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant health issue in Indonesia, with eleven provinces reporting a Case Fatality Rate (CFR) exceeding 1 percent. This community service activity aims to expand the utility of the SIAGA DBD application at Puskesmas Wagir, Malang Regency, in response to the high incidence of DHF in the area. Through training health workers and community cadres, the initiative aims to enhance the real-time reporting and monitoring of DHF cases. The implementation methods include coordination with the health office, surveying potential users, adding educational content, and providing training for health workers and community cadres. Results indicate an increase in participation in using the application, although this remains limited to a few areas. Evaluations indicate that the training was successful in improving understanding of the application, and cadres expressed confidence in utilizing the app for DHF monitoring. Socialization throughout the villages is necessary so that the SIAGA DBD application can be utilized more widely. For that reason, the development of an accurate village database will be necessary to enhance the application's effectiveness.